2009
DOI: 10.1117/1.3094746
|View full text |Cite
|
Sign up to set email alerts
|

Cure-induced photoresist distortions in double patterning

Abstract: Many processes are under evaluation as simplifications to current double patterning methods. Reduction in process complexity and cost may be achieved by use of track-based photoresist stabilization methods that eliminate one etch step by allowing a second resist to be patterned over a first resist. Examples of stabilization methods using numerous curing processes have been reported. At least some resist shrinkage during stabilization appears to be generally observed for these methods. We evaluate the link betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Increasing efforts in this area center on double imaging processes in which two or more independent lithographic patterns are generated in sequentially applied resist films, then transferred in a single etch step. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In previous reports, 15,16 we demonstrated that 172 nm cure stabilization, when properly implemented, can result in superior retention of photoresist profiles compared to broadband UV curing (Fig. 1).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Increasing efforts in this area center on double imaging processes in which two or more independent lithographic patterns are generated in sequentially applied resist films, then transferred in a single etch step. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In previous reports, 15,16 we demonstrated that 172 nm cure stabilization, when properly implemented, can result in superior retention of photoresist profiles compared to broadband UV curing (Fig. 1).…”
Section: Introductionmentioning
confidence: 70%
“…19 Details of the simulation approach have been described in a previous report. 16 Fig. 2a illustrates the experimental correlation between 172 nm cure dose and volumetric shrinkage as measured using offsets between dose-linearity curves of uncured and cured resist patterns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,15,16,18 To assess shrinkage in XP-7600A, we have employed the exposure latitude curve offset approach described elsewhere. [14][15][16] This method allows estimation of shrinkage for all CDs within an exposure latitude range of interest for a given line-space target. Results for XP-7600A are summarized in Fig.…”
Section: Resist Shrinkage During Cure Processingmentioning
confidence: 99%
“…A parallel set of studies developed fundamental linkages between shrinkage and distortion, and highlighted the need for curable resist materials with very low cure shrinkage. 15,16 Here, we show that use of resist materials designed for cure can greatly improve the lithographic performance of the 172 nm based process. We have developed new curable resists with low shrinkage and found that these materials are readily capable of patterning cross-grid contact holes at lithographic k 1 = 0.28, well beyond the practical k 1 limit for singleexposure contact patterning.…”
Section: Introductionmentioning
confidence: 98%